Script and society: the social context of writing practices in late Bronze Age Ugarit - Boyes, Philip J. (Crews Ser., 2021)
Cover -- Book title -- Copyright -- Table of Contents -- Acknowledgements -- Part I. Background, theory and methods -- 1. Introduction: Ugarit and its scripts -- 2. The social archaeology of writing -- Part II. Late Bronze Age writing practices in regional context -- 3.Writing in the Bronze Age Levant -- 4.Standardisation, vernacularisation and the emergence of alphabetic cuneiform -- 5.Influence and innovation: networks of writing practice and culture -- Part III. Writing and society at Ugarit -- 6.The contexts of writing at Ugarit -- 7.Writing and the social construction of place -- 8.Who wrote? Literacy in Ugarit -- 9.Writing practices and minority communities -- 10.Social change in Late Bronze Age Ugarit -- 11.Writing practices and elite identity: imperialism, resistance and vernacularisation -- 12.The impact and legacy of alphabetic cuneiform -- 13.Conclusion: the social context of writing practices at Ugarit -- Bibliography.